Pengurangan Kecemasan pada Ibu Hamil dengan Prenatal Gentle Yoga dan Teknik Pernafasan Nadhi Sodhana - Sri Utami Subagio; Rt. Miki Yulieti Pertasari; Fadhila Azkiya; Refi Lindawati; Nurseha Nurseha (Jurnal Penelitian Kesehatan SUARA FORIKES, 2024)
Psychological changes in pregnant women in each trimester often cause significant anxiety. However, many pregnant women do not yet know about non-pharmacological efforts to overcome this anxiety. This study aimed to evaluate the effectiveness of prenatal gentle yoga and Nadhi Sodhana breathing techniques in reducing anxiety in pregnant women. This study used a one group pre-test and post-test design. Before the intervention, a pre-test was conducted to assess the level of anxiety using the Perinatal Anxiety Screening Scale (PASS). After that, participants were given intervention in the form of prenatal gentle yoga and Nadhi Sodhana breathing techniques for 4 weeks with a frequency of 2 times a week. After the intervention, a post-test was conducted to evaluate changes in anxiety levels. The results showed a significant decrease in the level of anxiety in pregnant women after the intervention. Based on the pre-test results, most respondents (33.3%) experienced mild anxiety. After the intervention, the post-test results showed that most participants (33.3%) did not experience anxiety. Data analysis using paired samples t-test showed a significant difference with a p value = 0.000. Furthermore, it was concluded that prenatal gentle yoga and Nadhi Sodhana breathing techniques are effective in reducing anxiety levels in pregnant women.Keywords: pregnant women; anxiety; Nadhi Sodana breathing; prenatal gentle yoga ABSTRAK Perubahan psikologis ibu hamil di setiap trimester sering menyebabkan kecemasan yang signifikan. Namun, banyak ibu hamil yang belum mengetahui upaya non-farmakologis untuk mengatasi kecemasan tersebut. Penelitian ini bertujuan untuk mengevaluasi efektivitas prenatal gentle yoga dan teknik pernafasan Nadhi Sodhana dalam mengurangi kecemasan pada ibu hamil. Penelitian ini menggunakan rancangan one group pre test and post test. Sebelum intervensi, dilakukan pre test untuk menilai tingkat kecemasan menggunakan Perinatal Anxiety Screening Scale (PASS). Setelah itu, partisipan diberikan intervensi berupa prenatal gentle yoga dan teknik pernafasan Nadhi Sodhana selama 4 minggu dengan frekuensi 2 kali seminggu. Setelah intervensi, dilakukan post test untuk mengevaluasi perubahan tingkat kecemasan. Hasil penelitian menunjukkan penurunan signifikan pada tingkat kecemasan ibu hamil setelah intervensi. Berdasarkan hasil pre test, sebagian besar responden (33,3%) mengalami kecemasan ringan. Setelah intervensi, hasil post test menunjukkan bahwa sebagian besar partisipan (33,3%) tidak mengalami kecemasan. Analisis data menggunakan paired samples t-test menunjukkan adanya perbedaan signifikan dengan nilai p = 0,000. Selanjutnya disimpulkan bahwa prenatal gentle yoga dan teknik pernafasan Nadhi Sodhana efektif dalam menurunkan tingkat kecemasan pada ibu hamil.Kata kunci:  ibu hamil; kecemasan; pernafasan Nadhi Sodana; prenatal gentle yoga